FAKTOR FAKTOR RASIO KEUANGAN YANG MEMPENGARUHI CASH HOLDINGS: Pengaruh leverage, profitability, firm size, sales growth, operating cash flow dan tangible assets on cash holdings - Hermanto; Mesy (AKUNTANSI DEWANTARA, 2023)
This study is used to determine the effect of leverage, profitability, firm size, sales growth, operating cash flow and tangible assets on cash holdings in food and beverages sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The sampling technique used in this study was purposive sampling, with a total sample data used of 42 data from 7 entities in the food and beverage subsector. This study applies multiple linear regression as an analytical technique. The results of this study finds that: (1) Leverage, profitability and tangible assets have a negative and significant effect on cash holdings, (2) Company size and sales growth don’t effect cash holdings, (3) Operating cash flow effects positively on cash holdings. This research is useful for investors to be used as a reference source in making investment decisions as well as useful for company management in improving company performance in managing and holding cash, and also contributing to companies, especially the food and beverages sub-sector in the welfare of the Indonesian economy. As for the writer, this research is useful to deepen the researcher's insight into the factors of financial ratios that influence cash holdings.